2018
DOI: 10.1111/1365-2745.13019
|View full text |Cite
|
Sign up to set email alerts
|

Reassociation of an invasive plant with its specialist herbivore provides a test of the shifting defence hypothesis

Abstract: The shifting defence hypothesis (SDH) predicts that after invasive plants are introduced to new ranges, they will evolve reduced resistance to specialist herbivores and increased resistance to generalist herbivores because they can escape from specialists but are still attacked by generalists in their nonnative ranges. For this to be true, the subsequent introduction of native specialist herbivores should reverse the above evolutionary processes, but evidence collected so far is scarce. Here, we address this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 74 publications
(107 reference statements)
3
25
0
Order By: Relevance
“…This would indicate that such a trade‐off leading to lower competitive ability under biological control management has evolved after only one to two decades (i.e., selection on the total biomass: Q SC‐h > F SC‐h ), but additional bioassays are needed to substantiate such trade‐offs. A very recent study found a higher defence level in O. communa ‐infested A. artemisiifolia populations than uninfested populations in China (Wan, Huang, Yu, & Peng, ), which is well in line with our findings. Our study does support the EICA hypothesis associated with invasion success (Blossey & Nötzold, ; Bossdorf, ), however, the results also show that the initially evolved increased competitive ability after the introduction into a new region can also be lost again quickly with the re‐association of enemies, in this case specialize herbivores introduced for biological control (Joshi & Vrieling, ; Müller‐Schärer et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…This would indicate that such a trade‐off leading to lower competitive ability under biological control management has evolved after only one to two decades (i.e., selection on the total biomass: Q SC‐h > F SC‐h ), but additional bioassays are needed to substantiate such trade‐offs. A very recent study found a higher defence level in O. communa ‐infested A. artemisiifolia populations than uninfested populations in China (Wan, Huang, Yu, & Peng, ), which is well in line with our findings. Our study does support the EICA hypothesis associated with invasion success (Blossey & Nötzold, ; Bossdorf, ), however, the results also show that the initially evolved increased competitive ability after the introduction into a new region can also be lost again quickly with the re‐association of enemies, in this case specialize herbivores introduced for biological control (Joshi & Vrieling, ; Müller‐Schärer et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Chlorogenic acid was measured according to the methods described by Jinlong Wan (2019) [ 85 ]. A total of 0.05 g of powered sample was immersed in 5 mL of methanol-0.4% phosphoric acid solution.…”
Section: Methodsmentioning
confidence: 99%
“…Two solvent systems of the mobile phase: solvent A, acetonitrile/0.4% phosphoric acid (10:90, v:v); solvent B, 100% acetonitrile. The HPLC operating procedures was the same as that described in Jinlong Wan (2019) [ 85 ]. Chlorogenic acid concentrations of samples were calculated in relation to standard curves generated with relevant standards.…”
Section: Methodsmentioning
confidence: 99%
“…This result could be due to the shorter generation time of the antagonist as compared to its host plant, leading to a more virulent antagonist genotype (Kaltz et al 1999), or due to its oligophagous nature, which allows Ophraella to deal with a large diversity of plant defense chemicals (Ali and Agrawal 2012). The fact that the Ambrosia genotype only differed for total leaf area consumed by the larvae, but did not influence survival and developmental time, or the weight of the herbivore, may indicate that Ophraella can compensate for observed differences in secondary plant metabolites in Ambrosia (Fukano and Yahara 2012;Sun and Roderick 2019;Wan et al 2019) by adapting their feeding rate (Müller et al 2006). Significant Ambrosia-Ophraella G × G interactions were found only for two out of 13 variates measured, i.e., L2 survival and dry weight of adults.…”
Section: Ambrosia-ophraella Genotype Interactionsmentioning
confidence: 99%